106 Effect of Complications Within 90 Days on Cost-Utility Following Elective Surgery for Degenerative Lumbar Spine Disease. (August 2016) - Chotai, Silky; Sivaganesan, Ahilan; Parker, Scott L.; Wick, Joseph; Stonko, David P.; McGirt, Matthew J.; Devin, Clinton J.
Abstract : INTRODUCTION: Current health care systems are rapidly transitioning from the "fee-for service" to the "pay-for performance" model. With this paradigm shift, the providers and payers are constantly striving to determine tools to provide cost-effective and high-quality patient care. Therefore, it is vital to account for the complications and their effects on the cost and quality of life. We set forth to determine the cost-utility associated with complications after lumbar spine surgery. METHODS: Total 407 patients undergoing elective surgery for degenerative lumbar pathology enrolled in the prospective longitudinal registry were included in the study. PROs: Oswestry Disability Index (ODI), numeric rating scale-Back and leg pain (BP, LP), general health (SF-12), and quality-of-life scores EQ-5D were recorded at baseline and 2 years after surgery. Two-year back-related medical resource utilization, missed work, and health state values (quality-adjusted life-years [QALYs], calculated from the EQ-5D with US valuation using the time-weighted area under the curve approach) were assessed. Mean 2-year cost per QALY gained after surgery was assessed. The patients were divided into groups with and without complications to compare the QALYs gained and the cost-utility in these groups. RESULTS: Fourteen percent (n = 58) of patients developed complications within 90 days after surgery. Most frequent surgical complication was surgical site infection (4.2%, n = 17), 1.5% (n = 6) had deep surgical site infections. There was a significant improvement in pain (BP, LP), disability (ODI), and general health scores (EQ-5D and SF-12) in both groups at postoperative 2 years ( P < .0001). Patients with complications had lower mean cumulative 2-year QALY gained compared with those without complications (0.49 vs 0.57, P = .36). Cost-per-QALYs gained in patients with and without complications was $70 822 vs $45 831 ( P = .03). CONCLUSION: Lumbar surgery provided a significant improvement in outcomes and gain in health state utility regardless of the occurrence of complications within the 90-day global period. The cost-utility, which was higher in patients with complications, was $70 822, which is within the range of commonly accepted threshold of willingness to pay. Clearly, measures focused on prevention of complications to reduce the cost and increase cost-utility.